Integrated delivery of school health interventions through the school platform: Investing for the future. - Laura J Appleby; Gemechu Tadesse; Yonas Wuletawu; Nigussie G Dejene; Jack E T Grimes; Michael D French; Askale Teklu; Berhanu Moreda; Nebiyu Negussu; Biruck Kebede; Elodie Yard; Iain Gardiner; et al. (Public Library of Science (PLoS), 2019)
School health and nutrition (SHN) programmes are recognized as a significant contributor to both health and education sector goals. The school system offers an ideal platform from which to deliver basic health interventions that target the most common health conditions affecting school-age children (SAC) in low-income countries, leading to improved participation and learning outcomes. However, governments require evidence to cost, design, and implement these programmes. In Ethiopia, prevalent health conditions affecting SAC's education participation and learning outcomes include infection with soil-transmitted helminths (STHs), hunger, and malnutrition. In recognition of the multiple issues affecting the health and education of SAC, the government has taken a proactive approach, coordinating an integrated SHN programme designed to be implemented in partnership and monitored and financed through a single, integrated mechanism. The programme, known as the Enhanced School Health Initiative (ESHI), integrates three complimentary health interventions: deworming; school feeding; and provision of a water, sanitation, and hygiene (WASH) package in schools, which in delivery aim to maximize the benefits of each of the individual components. Operational research surrounding the ESHI programme includes both qualitative and quantitative analyses. Here, we present an overview of the ESHI programme and its genesis. We also introduce three additional supporting papers that provide in-depth analyses of key findings, including the baseline situational analysis, the costs, and community perceptions of the programme. The findings from ESHI provide initial evidence to develop an understanding of the related costs and synergies of integrating multiple health interventions onto a single platform. The work has translated into strengthened institutional capacity and improved cross-sectoral coordination. The government is now committed to supporting 25 million school children in Ethiopia through SHN. The ESHI model serves as a reference point for other countries looking to scale up targeted SHN interventions.